2022
DOI: 10.3389/fmats.2022.842887
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Microstructure Evolution and Fractal Features of Expansive Soil Improved by MICP Method

Abstract: Experimental study on one-dimensional consolidation and scanning electron microscope imaging of expansive soil improved by MICP method has been carried out, by using WG type consolidator and electron scanning microscope. Theoretical analysis on microstructure evolution process of improved expansive soil has been carried out based on fractal theory and damage theory. Through the research, the influence mechanism of cementation and filling effect of calcium carbonate precipitation on the microstructure of improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…According to the existing studies in our group, it was found that the best improvement of soil samples was achieved at a volume ratio of 1:2 between the bacterial solution and the cementation solution in the MICP process (Tian et al, 2022;Su et al, 2022). Therefore, the volume ratio of bacterial solution to cementation solution per unit mass of soil sample was controlled to 1:2.…”
Section: Preparation Of Specimensmentioning
confidence: 99%
“…According to the existing studies in our group, it was found that the best improvement of soil samples was achieved at a volume ratio of 1:2 between the bacterial solution and the cementation solution in the MICP process (Tian et al, 2022;Su et al, 2022). Therefore, the volume ratio of bacterial solution to cementation solution per unit mass of soil sample was controlled to 1:2.…”
Section: Preparation Of Specimensmentioning
confidence: 99%
“…The experimental study of using microorganisms to improve unfavorable soil makes it possible to apply this method to engineering. Scholars have used MICP technology to improve unfavorable soil to varying degrees, including sand [ 40 , 41 , 42 ], silt [ 43 , 44 , 45 ], loess [ 46 , 47 , 48 , 49 , 50 ], expansive soil [ 51 , 52 , 53 , 54 ], and mucky soil [ 55 , 56 ], using this method, and the unconfined compressive strength and cohesion of the soil are significantly improved, which can be used in engineering practice. In the field of geotechnical engineering, the research results of MICP on soil improvement can be used for foundation reinforcement [ 57 , 58 , 59 ], earth dam reinforcement [ 60 ], wind prevention, sand fixation [ 61 ], reservoir bottom anti-seepage, and anti-seepage curtains [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a new foundation reinforcement method, microbially induced calcite precipitation (MICP) technology has a potential application value in the fields of liquefiable sand layers (Riveros and Sadrekarimi, 2020), roadbeds (Xiao et al, 2022), and foundation pit slope reinforcement (Cheng et al, 2021). Compared with the traditional cement reinforcement method, the MICP treatment method is environmentally friendly, has low energy consumption, and is sustainable (Wang et al, 2017;Castro-Alonso et al, 2019;Su et al, 2022). In island construction, compared to traditional cement solidification, MICP has two major advantages: the first is the abundant Cl − and SO 4 2in the marine environment that will cause corrosion to ferroconcrete but have little impact on MICP treatment (Saleem et al, 1996); the second is the slightly alkaline environment of the ocean that is conducive to the reaction of microorganisms (Stocks-Fischer et al, 1999).…”
mentioning
confidence: 99%